Editorial. Issue 6 (5th February 2015) - FELLEISEN, MATTHIAS
<x content-type="archive" xml:space="preserve">Abstract</x> Over the past six months, we have transitioned to a new leadership team. We are now saying goodbye to Benjamin Pierce, who faithfully served as co-Editor in Chief since 2012, and welcome Jeremy Gibbons from the University of Oxford as new co-Editor in Chief.